1993
DOI: 10.1111/j.1600-0722.1993.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition, adhesion, and agglutination properties of saliva in burning mouth syndrome

Abstract: Resting and stimulated whole saliva and parotid saliva of men and pre‐ and post‐menopausal women with burning mouth syndrome (BMS) and their matched controls were studied. Women with BMS had slightly, but not significantly, higher flow rates than their controls. The total protsein concentration in stimulated saliva of women with BMS was significantly lower than that of controls. This difference was not associated with the flow rate. The proportional amount of sialic acid, used as an indicator of mucin concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
2
18
2
2
Order By: Relevance
“…11 The most commonly reported range has been 0.7% to 4.6% 11 , however, rates as high as 14.8% have also been estimated. 18 In present study we found 1.2% prevalence.…”
Section: Discussionsupporting
confidence: 51%
“…11 The most commonly reported range has been 0.7% to 4.6% 11 , however, rates as high as 14.8% have also been estimated. 18 In present study we found 1.2% prevalence.…”
Section: Discussionsupporting
confidence: 51%
“…Magnesium level did not change in the saliva stimulated in patients with BMS. Tammiala‐Salonen and Soderling (1993) found no decrease in protecting and lubricating properties of saliva in patients with BMS, although they did find significantly lower total protein concentration in the stimulated saliva of women with BMS as well as higher concentration of sialic acid. Lundy et al (1997) could not find any difference in the major parotid glycoproteins between patients with BMS and controls.…”
Section: Discussionmentioning
confidence: 77%
“…One study demonstrated a reduction in postmenopausal parotid flow rate (resting and stimulated); 55 another study found no differences in resting saliva in postmenopausal patients with burning tongues and those without 56 . Yet, another study investigated resting and stimulated whole saliva and parotid saliva in pre‐ and postmenopausal women and in men with BMS and matched controls 57 . Women with BMS had slightly, but not significantly, higher flow rates than their controls.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%